Management of Central Nervous System Infections, Vientiane, Laos, 2003–2011 - Audrey Dubot-Pérès; Mayfong Mayxay; Rattanaphone Phetsouvanh; Sue J. Lee; Sayaphet Rattanavong; Manivanh Vongsouvath; Viengmon Davong; Vilada Chansamouth; Koukeo Phommasone; Catrin Moore; Sabine Dittrich; Olay Lattana; et al. (Emerging Infectious Diseases, 2019)
During 2003–2011, we recruited 1,065 patients of all ages admitted to Mahosot Hospital (Vientiane, Laos) with suspected central nervous system (CNS) infection. Etiologies were laboratory confirmed for 42.3% of patients, who mostly had infections with emerging pathogens: viruses in 16.2% (mainly Japanese encephalitis virus [8.8%]); bacteria in 16.4% (including Orientia tsutsugamushi [2.9%], Leptospira spp. [2.3%], and Rickettsia spp. [2.3%]); and Cryptococcus spp. fungi in 6.6%. We observed no significant differences in distribution of clinical encephalitis and meningitis by bacterial or viral etiology. However, patients with bacterial CNS infection were more likely to have a history of diabetes than others. Death (26.3%) was associated with low Glasgow Coma Scale score, and the mortality rate was higher for patients with bacterial than viral infections. No clinical or laboratory variables could guide antibiotic selection. We conclude that high-dependency units and first-line treatment with ceftriaxone and doxycycline for suspected CNS infections could improve patient survival in Laos.